Analisis Dan Perancangan Sistem Informasi Penilaian Kinerja PTT Pada Dinas Komunikasi Dan Informatika Kota Jambi - Marhamah, Marhamah; Effiyaldi, Effiyaldi (LPPM Universitas Dinamika Bangsa, 2020)
The communication and information departement in Jambi had not have a technology in Temporary Employees’ information working assesment system which was not arranged for making easy working assesment and processing the data. In processing working assesment was done by using form of working assesment such as paper. To know the development of Temporary Employees’ working assesment, the Head of Officer should recapitulate the result of each Temporary Employees’ working assesment used Ms.Office and Ms.Word. Thus, the aim of the writer to analyze and design the tenporary Employees’ information assesment system by applying the web system. The ouline of this research was consisted of identification of problem, literature of study, Data collection, analysis and the design, prototype design, and report. The method of system development, the writer did the Diagrram Konteks design, Level nol (zero) diagram, Level 1 diagram, Process 1.0 and Prototype. Temporary Employees’ information working assesment system could do working assesment process and processing the data well so that it could affect the effectivity and efficiency the working process assesment and shorten the time and also minimize the mistakes when input the data. The writer also hope this system could develop more and the officer could operate this system. In designing the prototype, this system had not seen the security data problem, so for the next research can be completed with security data system.